2018
DOI: 10.3389/fimmu.2018.01121
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptors Expressed on Myeloid Cells 2 Promotes Corneal Resistance Against Pseudomonas aeruginosa by Inhibiting Caspase-1-Dependent Pyroptosis

Abstract: Triggering receptors expressed on myeloid cells 2 (TREM2) is a novel cell surface receptor and functions as an immunomodulatory receptor in infectious diseases. In this study, we investigated the function and regulatory mechanism of TREM2 in Pseudomonas aeruginosa (P. aeruginosa) keratitis. We found that P. aeruginosa keratitis was more severe in Trem2−/− versus wild type C57BL/6 mice as indicated by the increased clinical scores, bacterial load, and cornea pathology. The exacerbated disease progression caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…However, activation of microglial CR1 induces neurotoxic cytokines and reactive oxygen species (53). Although TREM2 is found to upregulate complement components during aging (69), it can inhibit inflammasome activation (67). CD33 may induce NLRP3 inflammasome assembly (48).…”
Section: Role Of Tlr4 Signaling In Alzheimer's Disease Brainmentioning
confidence: 99%
“…However, activation of microglial CR1 induces neurotoxic cytokines and reactive oxygen species (53). Although TREM2 is found to upregulate complement components during aging (69), it can inhibit inflammasome activation (67). CD33 may induce NLRP3 inflammasome assembly (48).…”
Section: Role Of Tlr4 Signaling In Alzheimer's Disease Brainmentioning
confidence: 99%
“…Similarly, knockout mice for Tyrobp , the other gene commonly associated with NHD encoding the adapter protein for TREM2, exhibits increased autoantibodies (e.g., anti-double stranded DNA) and IgG2a/3 levels, and defects of NK and T cells' regulatory function. Recently, Qu et al (15) found an increased production of pro-inflammatory cytokines (IL-1β, IL-18, and CXCL2) and overactivation of the NLRP3 inflammasome pathway in Trem2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is a type of proinflammatory programmed cell death, which may be involved in the early process of corneal resistance to infection and removal of P. aeruginosa as previous reported. 31 Exoproteins (including superantigens and cytolysins) induced proinflammatory signals from epithelial cells have been well characterized in Staphylococcus aureus infection. 32 The pathogenesis of P. aeruginosa at the corneal epithelial surface remains unclear.…”
Section: Discussionmentioning
confidence: 99%